The upper values of plasma creatine kinase of professional soccer players during the Brazilian National Championship - Lazarim, F. L.; Antunes-Neto, J. M. F.; da Silva, F. O. C.; Nunes, L. A. S.; Bassini-Cameron, A.; Cameron, L. C.; Alves, A. A.; Brenzikofer, R.; Vaz de Macedo, D. (Journal of Science and Medicine in Sport, 2009)
The current schedule of the Brazilian Soccer Championship may not give players enough recovery time between games. This could increase the chances of muscle damage and impaired performance. We hypothesized that plasma creatine kinase (CK) activity could be a reliable indirect marker of muscle overload in soccer players, so we sought to identify the reference values for upper limits of CK activity during a real-life elite competition. This study analyzed changes in plasma CK activity in 128 professional soccer players at different times during the Brazilian Championship. The upper limits of the 97.5th and 90th percentiles determined for CK activity were 1.338 U/L and 975 U/L, respectively, markedly higher than values previously reported in the literature. We also evaluated a team monthly throughout the Championship. The upper limit of the 90th percentile, 975 U/L, was taken as the decision limit. Six players showing plasma CK values higher than this were asked to decrease their training for 1 week. These players presented lower CK values afterwards. Only one player with a CK value higher than the decision limit (1800 U/L 1 day before a game) played on the field and was unfortunately injured during the game. The CK activity in all the other players showed a significant decrease over the course of the Championship, and the values became more homogeneous at the end. The results presented here suggest that plasma CK upper limit values can be used as a practical alternative for early detection of muscle overload in competing soccer players.